MEDICAL ETHICS IN MILITARY MEDICAL SETUPS: Medical Ethics - Fayyaz, Dr Muhammad (Pakistan Armed Forces Medical Journal, 2018)
Regarding the editorial by Brigadier Tariq Mahmood Ahmad on ‘Role of Medical Ethics in Developing Caring Health Professionals’ (PAFMJ Vol. 67, No. 6, December 2017), there is no second opinion on importance of medical ethics in modern practice of medicine. The students and practitioners of medicine at all levels should know - at least - the ethical parameters of their interactions with patients. The introduction to certain topics like sanctity of life, informed consent, privacy & confidentiality, pharmaphysician interactions and therapeutic misconception etc. cannot be over-emphasized1. It’s a fact that ethical perspectives from west cannot be used en-block because of vast ethnic, religious, cultural and linguistic difference and concept of right and wrong have different grounds. To be away from a class-rooms & to be effective in practical life, we need to indigenize them2. To do so, the availability of trained local workforce in this field is needed & that will be able to play a role, to better integrate the subject in academic sense and build the capacity of health care providers at all levels; undergraduate as well as